Biomechanics of Aortic Dissection: A Comparison of Aortas Associated With Bicuspid and Tricuspid Aortic Valves. Issue 15 (4th August 2020) - Chung, Jennifer C.‐Y.; Wong, Edwin; Tang, Mingyi; Eliathamby, Daniella; Forbes, Thomas L.; Butany, Jagdish; Simmons, Craig A.; Ouzounian, Maral
Abstract : Background: Current methods for aortic dissection risk assessment are inadequate for patients with ascending aortic aneurysms associated with either bicuspid aortic valves (BAVs) or tricuspid aortic valves (TAVs). Biomechanical testing of aortic tissue may provide novel insights and biomarkers. Methods and Results: From March 2017 to August 2019, aneurysmal ascending aortas (BAV=23, TAV=23) were collected from elective aortic surgery, normal aortas from transplant donors (n=9), and dissected aortas from surgery for aortic dissection (n=7). These aortas underwent delamination testing in simulation of aortic dissection. Biaxial tensile testing was performed to determine modulus of elasticity (aortic stiffness), and energy loss (a measure of efficiency in performing the Windkessel function). Delamination strength ( S d ) was lowest in dissected aortas (18±6 mN/mm) and highest in normal aortas (58±16 mN/mm), and aneurysms fell in between, with greater S d in the BAV group (37±10 mN/mm) than the TAV group (27±10 mN/mm) ( P <0.001). Bicuspid aortopathy was associated with greater stiffness ( P <0.001), while aneurysms with TAV demonstrated greater energy loss ( P <0.001). S d decreased by 7.8±1.2 mmol/L per mm per decade of life ( r 2 =0.45, P <0.001), and it was significantly lower for patients with hypertension ( P =0.001). S d decreased by 6.1±2.1 mmol/L per mm with each centimeter increase in aortic diameter ( r 2 =0.15, P =0.007). Increased energy loss was associated with decreased S d ( r 2 =0.41), whereas there was no relationship between S d and aortic stiffness. Conclusions: Aneurysms with BAV had higher S d than those with TAV, suggesting that BAV was protective. Energy loss was lower in aneurysms with BAV, and inversely associated with S d, representing a potential novel biomarker.